Distribution of Dichlorodiphenyltrichloroethane (DDT) and Hexachlorocyclohexane (HCH) in Urban Soils and Risk Assessment - Bhupander Kumar; Meenu Mishra; VK Verma; Sanjay Kumar; CS Sharma (MDPI AG, 2013)
This study deals with the distribution of DDTs and HCHs in urban soils, their possible sources and probabilistic human and environmental health risk. The average concentrations of total HCHs and total DDTs in the soils were in the range of 0.56-8.52 µg kg-1 and 0.54-37.42 µg kg-1, respectively, which were lower than guideline limits.The compositional analysis of HCH isomers reflect contaminations from recent usage. However, isomeric ratios between DDT, DDE and DDD, indicate anaerobic degradation of DDT and contaminations from aged DDT. Human and environmental health risk assessment was carried out by the estimation of life time average daily dose (LADD), incremental life time cancer risk (ILCR) and non carcinogenic health hazard quotient (HQ). LADD of total pesticides (HCH and DDT) for human adults and children was ranged between 3.3x10-9 - 6.6x10-8 mg kg-1 d-1 and 1.7x10-8 - 3.4x10-7 mg kg-1 d-1, respectively. The cumulative incremental life time cancer risk (ILCR) for adults and children was ranged from 5.1x10-9 to 4.6x10-8 and 2.6x10-8 to 2.4x10-7, respectively. The HQ was ranged between 1.8x10-6 - 1.4x10-4 and 9.5x10-6 - 7.2x10-4, respectively for adults and children. These estimated ILCR and HQ were within the safe acceptable limits, indicating negligible risk to the residents of the study area.